(untitled) (Economic and Political Thought, 2022)
The research problem undertaken by the author is the activity of social enterprises which, despite the negative impact of the pandemic, have a positive impact on minimizing the effects of the pandemic. The aim of the article is to verify the hypothesis that a social enterprise located in the social market economy may mitigate the effects of a pandemic by taking additional measures for recipients in connection with COVID-19. The premise for taking up the research topic is the research gap in the literature in the field of combining these two pro-social concepts and assessing how a social enterprise can complement the bottom-up deficiencies resulting from the weakness of the social market economy in Poland. To verify the hypothesis, the author used the research for the doctoral dissertation carried out from July 22, 2021 to October 29, 2021. The subject of the study was 379 entities from the database of 1630 social enterprises. The key finding of the study is that social enterprises suffering from the effects of the pandemic are also able to minimize them at the same time.